1993
DOI: 10.1152/jn.1993.69.5.1774
|View full text |Cite
|
Sign up to set email alerts
|

Anoxia-induced LTP of isolated NMDA receptor-mediated synaptic responses

Abstract: 1. The effects of an anoxic-aglycemic episode (1-3 min) on the pharmacologically isolated N-methyl-D-aspartate (NMDA)-mediated responses were examined in CA1 pyramidal hippocampal neurons in vitro. 2. An anoxic-aglycemic episode induced a long term potentiation (LTP) of the NMDA receptor-mediated field excitatory post-synoptic potentials (EPSPs). This LTP, referred to as anoxic LTP, was observed in the presence of 1) a normal Mg2+ concentration [+40.1 +/- 5% (mean +/- SE)], 2) a low Mg2+ concentration (+52.2 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 0 publications
2
30
0
1
Order By: Relevance
“…Such long-term OGD is known to cause significant neuronal damage. Quite brief episodes of OGD are usually used to induce long-term potentiation-like events in CA1 pyramidal neurons of acute hippocampal slices [21,22] and are not considered to be destructive. Recently, brief transient periods of OGD (up to 10 min) have been shown to cause rapid ultrastructural changes in synaptic apparatus in hippocampal slice cultures [3], presumably presenting morphological substrate for post-ischemic long-term potentiation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Such long-term OGD is known to cause significant neuronal damage. Quite brief episodes of OGD are usually used to induce long-term potentiation-like events in CA1 pyramidal neurons of acute hippocampal slices [21,22] and are not considered to be destructive. Recently, brief transient periods of OGD (up to 10 min) have been shown to cause rapid ultrastructural changes in synaptic apparatus in hippocampal slice cultures [3], presumably presenting morphological substrate for post-ischemic long-term potentiation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Mild ischemia causes overactivation associated with unregulated calcium inflow and consequent delayed neuronal death, whereas severe ischemia causes inactivation with transmission failure. 79 Synaptic failure as a result of NMDA receptor inactivation has been shown repeatedly in vitro 80,40 and in vivo, 79 and it has been associated with increased phosphorylation of the receptor. 81,82 However, coexisting damage of presynaptic functions and neuronal damage were not unequivocally refuted in any of the studies examining postsynaptic effects.…”
Section: Evidence Of Postsynaptic Failurementioning
confidence: 99%
“…Previous work has shown that application of a brief OGD to hippocampal slices results in a lasting increase of excitatory synaptic strength, mimicking theta burst-induced LTP and without effects on immediate cell survival (Crepel et al, 1993;Hammond et al, 1994;Hsu and Huang, 1997;Jourdain et al, 2002). This lasting synaptic potentiation was therefore called anoxic LTP.…”
Section: Axo-somatic Inhibitory Synapsesmentioning
confidence: 99%